Fatores que conduzem ou afastam os dentistas na realização de medidas preventivas em relação à cárie dentária : uma revisão sistemática e metassumarização - Suga, Uhana Seifert Guimarães (2013)
To perform a systematic review of qualitative studies and surveys on the factors that drive dentists toward and away from preventive measures in relation to dental caries. The following electronic databases were searched: BBO, Cochrane Library, EMBASE, Lilacs, MEDLINE, Scopus, Web of Science and York. We manually searched the references of full texts, as well as we retrieved and evaluated their citations using Google Scholar. Two reviewers independently evaluated titles and abstracts, and then full-texts manuscripts to determine study eligibility, assessed quality of the included studies and extracted data. Disagreements were resolved by consensus, and a third reviewer's opinion was sought if the disagreement persisted. Descriptive analysis of the included articles was conducted, and we bred themes of analysis, grouping the relevant findings, from which was calculated the frequency effect size (FES) and intensity effect size (IES) of studies. Of the 18.276 studies retrieved, 7 qualitative studies and 41 surveys were included (36.632 participants). The main themes identified were: biologicism (FES=27%), low pay for preventive procedures (FES=25%), trained professionals for more time (FES=22%), professional male (FES=19%), lack of awareness of patients the importance of prevention (FES = 17%), difficulty in treatment of small children (FES=12%), teamwork (FES=21%), professional development (graduate) (FES=12%), awareness of preventive work, preventive education (FES=10%) and motivation of parents (FES=4%). Studies varied in relation to methodological quality. The major factors identified that drive dentists away from performing preventive measures related to dental caries: biologicism, low pay for preventive procedures, trained professionals for more time, professional male, lack of awareness of patients the importance of prevention and difficulty in treatment of small children. Regarding the factors that drive toward prevention, we identified: teamwork, professional development (graduate), awareness of preventive work, preventive education and motivation of parents.